Rancang Bangun Sistem Informasi Koseling PIK-R Berbasis Web Studi Kasus SMA Negeri 1 Bekasi - Anjani, Citra Nur; Ramos, Samuel; Bani, Alexius Ulan (Yayasan Bina Internusa Mabarindo, 2024)
The Youth Information and Counseling Center (PIK-R) at SMA Negeri 1 Bekasi plays an important role in providing counseling services to students, but it is currently facing several challenges. Difficulties in organizing student counseling messages, the absence of a computerized system, and slow report generation are the main issues that need to be addressed. These conditions hinder the efficiency of counseling services, which should be faster and more structured. Therefore, this research aims to design a web-based information system that can improve the management efficiency of counseling services at PIK-R. Utilizing modeling methods such as Unified Modeling Language (UML) in the form of Use Case Diagrams, Activity Diagrams, Class Diagrams, and data normalization to maintain consistency and storage efficiency, this system is designed to provide an effective solution. The system is developed using the PHP programming language with the Laravel framework and a MySQL database, following the Waterfall approach. System testing is carried out using the BlackBox method to ensure all features function as required. With this information system, it is expected that the counseling process will become more organized, student data will be more easily accessed and managed, and report generation can be done more quickly and accurately.